Prevalence of inborn metabolismo erros detected by neonatal screening in the state from Piauí, Brazil: 2013-2019 (Research, Society and Development, 2022)
Objective: To assess the prevalence of Inborn Metabolism Errors (IMT) detected by neonatal screening in the state of Piauí from 2013 to 2019. Methods: We have information such as monthly data distribution, ethnicity and gender. This is a descriptive, quantitative and cross-sectional study, based on an analysis of the database of the Central Public Health Laboratory Dr Costa Alvarenga - LACEN, verifying the years resulting from implementation in accordance with the ordinance of each EIM. Results: There were 270,378 newborns screened from 2013 to 2019. During the study period, the following prevalences were obtained: DB 1:48, only in 2019; HAC 1:184, only in 2019; HC 1:185, with data collected in the study period 2013 to 2019; FC 1:242, from 2014 to 2019; sickle trait 1:946; sickle cell disease 1:1,507; alpha thalassemia 1:233,611 in Hemoglobinopathies, from 2014 to 2019; PKU 1:2,481, with data collected from 2013 to 2019. Conclusion: In this analysis, it was noticed that the state of Piauí has ​​a high prevalence in most of the analyzed diseases, which increases the importance of paying attention to these data, for future public attitudes towards better management of these diseases, as forms of diagnosis and early treatment.